2022
DOI: 10.1186/s40359-021-00714-3
|View full text |Cite
|
Sign up to set email alerts
|

Pre-surgery supportive and goal-oriented strategies are associated with lower post-surgery perceived distress in women diagnosed with breast cancer

Abstract: Background Psycho-oncology literature pointed out that individual health outcomes may depend on patients’ propensity to adopt approach or, conversely, avoidant coping strategies. Nevertheless, coping factors associated with postoperative distress remain unclear, unfolding the lack of tailored procedures to help breast cancer patients manage the psychological burden of scheduled surgery. In view of this, the present study aimed at investigating: 1. pre-/post-surgery distress variations occurring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Previous studies have noted that biopsychosocial support can improve clinical outcomes in the postoperative setting, including reducing the number and severity of complications and improving patients' recovery and prognosis. 12,13 The other reasons for hospital admission (fever/infection/neutropenia, functional status, and respiratory) were significantly higher among patients who did not participate in the BSP. It is possible that the program could affect patients' recovery during the treatment period, suggesting that screening and referrals increase the ability of an integrated model of care to manage patients' unmet needs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have noted that biopsychosocial support can improve clinical outcomes in the postoperative setting, including reducing the number and severity of complications and improving patients' recovery and prognosis. 12,13 The other reasons for hospital admission (fever/infection/neutropenia, functional status, and respiratory) were significantly higher among patients who did not participate in the BSP. It is possible that the program could affect patients' recovery during the treatment period, suggesting that screening and referrals increase the ability of an integrated model of care to manage patients' unmet needs.…”
Section: Discussionmentioning
confidence: 99%
“…After experiencing diferent degrees of psychological distress, patients choose to accept the fact of having cancer, including the acts of embracing the diagnoses and resigning themselves to it. A study has shown that patients who experience presurgery psychological distress can infuence postoperative functional recovery and prognosis [46]. Ohkura et al longitudinally tracked changes in the psychological status of patients undergoing esophagectomy at fve time points and showed that changes in patients' psychological status were signifcantly associated with changes in symptom experience and quality of life brought about by esophagectomy [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Identification of patients with high distress allows providers the opportunity to offer interventions aimed to decrease distress. A recent study by Taurisano et al [37] demonstrated that a pre-surgery intervention reduced post-op distress in patients with breast cancer. Similar interventions exist to reduce distress in breast cancer survivors [38].…”
Section: Discussionmentioning
confidence: 99%